Behaviors of Spherical and Nonspherical Particles in a Square Pipe Flow (Communications in Computational Physics, 2020)
The lattice Boltzmann method (LBM) for multicomponent immiscible fluidsis applied to the simulations of solid-fluid mixture flows including spherical or nonsphericalparticles in a square pipe at Reynolds numbers of about 100. A spherical solidparticle is modeled by a droplet with strong interfacial tension and large viscosity, andconsequently there is no need to track the moving solid-liquid boundary explicitly.Nonspherical (discoid, flat discoid, and biconcave discoid) solid particles are made byapplying artificial forces to the spherical droplet. It is found that the spherical particlemoves straightly along a stable position between the wall and the center of the pipe(the Segré-Silberberg effect). On the other hand, the biconcave discoid particle movesalong a periodic helical path around the center of the pipe with changing its orientation,and the radius of the helical path and the polar angle of the orientation increaseas the hollow of the concave becomes large.